Strategic Orientation and Performance of Small And Medium Enterprises (SMEs) in Sabah, Malaysia - Misek Umbaris, Yusak Yumboris @; Gisip, Imelda Albert; Ambad, Nabila Azwa (Journal of Social Transformation and Regional Development, 2020)
This paper seeks to examine the effects of strategic orientation (SO) to Small and Medium Enterprises (SMEs) performance in Sabah, Malaysia context. Specifically, the effects of two components of SO namely Market Orientation (MO) and Entrepreneurial Orientation (EO) towards SMEs performance in in Sabah, Malaysia context are discussed. In addition, Technology Orientation (TO) as moderator to the relationship between the two SO components and SMEs performance will also be deliberated. This paper is mainly based on secondary sources of information, through references and review of articles in selected journals pertaining to strategic orientation and SMEs performance. This paper highlights past studies on the relationship between the two main components of SO and its effects to SMEs performance. The reviews also address the related gaps from previous studies. The work of the researcher is genuine reference to published literatures and seeks to contribute to the development of knowledge by adapting and testing the moderating effect of technology orientation in the relationship between SO and SMEs performance.